Facile one pot synthesis of highly stable L-ascorbic acid coated magnetite nanoparticles dispersion - Yau, X.H. (Inst Materials Physics, 2017)
Magnetite nanoparticles had been synthesized through a simple one pot and ecofriendly method. Biocompatible and nontoxic L-ascorbic acid (LAA) was used as capping agent in the synthesis process to produce highly stable magnetite nanoparticle dispersion. The magnetite nanoparticles were characterized with various techniques. From X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDX) analysis, the results reveal that magnetite nanoparticles were synthesized without impurities. Spherical magnetite nanoparticles with average particle size of 11.1 nm coated with LAA was shown in both scanning electron microscope (SEM) and transmission electron microscope (TEM) images. Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) confirmed the LAA capped on the surface of magnetite nanoparticles, whereas Zeta potential shows the LAA coated magnetite nanoparticles were exhibit high stability with good dispersion. From vibrating sample magnetometer (VSM), the superparamagnetism of magnetite nanoparticles was confirmed. Possible mechanism of LAA capped on magnetite nanoparticles was proposed eventually. © 2017, Inst Materials Physics. All rights reserved.